Logistics support planning model in the conditions of limited resources - Simić, Nikola B.; Milenkov, Marjan A.; Milovanović, Vladimir R.; Sokolović, Vlada S.; Foltin, Pavel Ј.; Taksás, Balázs Ј. (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: The paper presents a model of logistics support planning in the conditions of limited logistic resources based on the prioritization of customer requirements and resource allocation. Decision-makers play a crucial role in the efficient and equitable allocation of resources as they prioritize among different user requirements. Methods: Requirement prioritization techniques that use nominal scale, ordinal scale, and ratio scale, and five methods for converting ranks into weighting coefficients have been applied to determine the degree of significance of user requirements. The Requirements triage method has been used for establishing relative priorities, while the heuristic algorithm determining the Kemeny median was used to consolidate individually ranked requests into a group rank. In order to balance opposing demands of users, consensus measures of group decision making were used. For obtaining an optimal planned solution of logistic support, the methods and techniques of resource allocation were applied.Results: A model for adaptive planning of logistics support in the conditions of limited resource capacities of the logistics system has been developed.Conclusion: The proposed model can be effectively applied in other areas of resource allocation.
Keywords: logistics planning; requirement prioritization; triage; converting ranks into weights; resource allocation